1980
DOI: 10.1210/jcem-50-6-1127
|View full text |Cite
|
Sign up to set email alerts
|

Domperidone, an Extracerebral Inhibitor of Dopamine Receptors, Stimulates Thyrotropin and Prolactin Release in Man

Abstract: Domperidone, an extracerebral dopamine receptor antagonist, was given im to 12 normal subjects and to a group of patients with subclinical hypothyroidism to study its effect on PRL and TSH secretion. Domperidone induced in all subjects a quick and marked increment of serum PRL. At 180 min, the levels remained high. A small but significant increase of TSH was also observed in normal as well as in hypothyroid subjects. Since domperidone does not cross the blood-brain barrier, the hormonal changes observed may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…Comparing morphine data with those obtained with dopamine antaggonists administration it is possible to observe similar ef fects with regard both to the degree of TSH increase, lower than that of PRL, and to enhancement of the TSH response to TRH [4,6]. Moreover, our preliminary data (not re ported) show that bromocriptine, a dopamine agonist, is able to blunt morphine-induced TSH and PRL release.…”
Section: Discussionsupporting
confidence: 71%
“…Comparing morphine data with those obtained with dopamine antaggonists administration it is possible to observe similar ef fects with regard both to the degree of TSH increase, lower than that of PRL, and to enhancement of the TSH response to TRH [4,6]. Moreover, our preliminary data (not re ported) show that bromocriptine, a dopamine agonist, is able to blunt morphine-induced TSH and PRL release.…”
Section: Discussionsupporting
confidence: 71%
“…Sowers et al [122] were probably the first to describe a slight elevation of serum TSH levels in euthyroid men following administration of metoclopramide. Their re sults were subsequently confirmed and expanded by other workers using metoclopramide [41,109,110], the related drug sulpiride [68,143] or the novel blocker, domperidone [20,67,94]. It soon became evident that the magnitude of the rise in the TSH levels is determined by several factors.…”
Section: Dopaminementioning
confidence: 74%
“…Separate studies with intramuscular or oral domperidone indicated that the drug had the same potency as metoclopramide in inducing prolactin release. [102][103][104] Based on these findings, it is unlikely that the different prolactin levels caused by the various antagonists are due to different affinities at the dopamine D 2 receptor, as domperidone and clebopride have comparable affinities (see Table 1) 1 . It is also unlikely that the various antagonists can differently modulate the release of dopamine from the tuberoinfundibular pathway, as dopamine D 2 autoreceptors are absent in this pathway.…”
Section: Hyperprolactinaemiamentioning
confidence: 98%